"Op die aarde net soos in die hemel": Matteus se eskatologie as die koninkryk van die hemel wat reeds begin kom het - Aarde, Andries van (HTS teologiese studies, 2008)
“On earth as it is in heaven”: Matthew’s eschatology as the kingdom of heaven that has come In the article time as both “imagined” and “experienced” is explained against the background of the first-century Mediterranean conceptualisation of time. This reading scenario is seen as over against a modern Eurocentric ethnocentric interpretation of the concept "apocalyptic- eschatology”. The aim of the article is to argue that Matthew’s narration of the demolition of the temple in Jerusalem concurs with his belief that the first followers of Jesus experienced the vision of the coming of the Son of man and that both these experiences are presented in Matthew as though Jesus’ crucifixion and resurrection are incidents of the past. Matthew’s eschatology centres on the view that the final consummation of time has already begun. The article explores the ethical appeal which is communicated through such an eschatological reading scenario. This appeal is summarised by Jesus’ words “On earth as it is in heaven”. The article consists of a conversation about core issues in mainstream interpretations of what Matthew’s eschatology could be within the narrative’s plot as it contextualised in formative Christianity and formative Judaism. The view assumed in this article is that the “time” and the experiences of Matthew’s church and those of Jesus and his disciples are considered to be integrated within the history of Israel.